A new strategy for simultaneous determination of 4-aminophenol, uric acid and nitrite based on a graphene/hydroxyapatite composite modified glassy carbon electrode1. Issue 65 (16th July 2015) - Lavanya, N.; Sudhan, N.; Kanchana, P.; Radhakrishnan, S.; Sekar, C.
<x xml:space="preserve">Abstract</x> A novel electrochemical sensor has been fabricated based on a graphene/hydroxyapatite composite modified GCE for the selective and simultaneous detection of 4-aminophenol, uric acid and nitrite ions (NO2−) by voltammetric method for the first time.